Safety and efficacy of teriflunomide in paediatric multiple sclerosis (TERIKIDS): a multicentre, double-blind, phase 3, randomised, placebo-controlled trial. Issue 12 (December 2021) - Chitnis, Tanuja; Banwell, Brenda; Kappos, Ludwig; Arnold, Douglas L; Gücüyener, Kivilcim; Deiva, Kumaran; Skripchenko, Natalia; Cui, Li-Ying; Saubadu, Stephane; Hu, Wenruo; Benamor, Myriam; Le-Halpere, Annaig; et al.
Summary: Background: Therapeutic options for children with multiple sclerosis are scarce. Teriflunomide is approved in more than 80 countries for the treatment of adults with relapsing multiple sclerosis. The TERIKIDS study examined the safety and efficacy of teriflunomide in children with relapsing multiple sclerosis. Methods: The TERIKIDS trial was a multicentre, phase 3, double-blind, parallel-group, randomised, placebo-controlled study conducted at 57 clinical centres in 22 countries in Asia, Europe, the Middle East, North Africa, and North America. The trial enrolled patients aged 10–17 years, diagnosed with relapsing multiple sclerosis and with at least one relapse in the year preceding screening or at least two relapses in the 2 years preceding screening. Patients were randomly assigned (2:1) to oral teriflunomide (dosage equivalent to 14 mg in adults) or matching placebo, using an interactive web and voice response system, for up to 96 weeks. Personnel in all sites and all patients were masked to study treatment in the double-blind period. Early entry into a subsequent 96-week open-label extension phase was possible before the end of the double-blind period for patients with confirmed clinical relapse or high MRI activity (at least five new or enlarged T2 lesions at week 24, followed by at least nine new or enlarged T2 lesions at week 36, or at least five new or enlarged T2 lesions at weeks 36 and 48, or at weeks 48 and 72). The primary endpoint was time to first confirmed clinical relapse by the end of the double-blind period. Key secondary imaging endpoints were number of new or enlarged T2 lesions and number of gadolinium-enhancing lesions per MRI scan. Efficacy endpoints were analysed in the intention-to-treat population, and safety was assessed in all patients randomly assigned to treatment and exposed to the double-blind study medication. This study is registered with ClinicalTrials.gov (trial number NCT02201108 ) and is closed to recruitment, but an additional optional open-label extension is ongoing. Findings: Between July 24, 2014, and the date of last patient visit on Oct 25, 2019, 185 patients were screened for eligibility, 166 (90%) were enrolled, and 109 were randomly assigned teriflunomide and 57 were randomly assigned placebo. 102 (94%) of 109 and 53 (93%) of 57 completed the double-blind period. Switch to the ongoing open-label extension because of high MRI activity was more frequent than anticipated in the placebo group (14 [13%] of 109 patients in the teriflunomide group vs 15 [26%] of 57 in the placebo group), decreasing the power of the study. After 96 weeks, there was no difference in time to first confirmed clinical relapse with teriflunomide compared with placebo (hazard ratio 0·66, 95% CI 0·39–1·11; p=0·29). Teriflunomide reduced the number of new or enlarged T2 lesions versus placebo by 55% (relative risk 0·45, 95% CI 0·29–0·71; p=0·00061), and the number of gadolinium-enhancing lesions by 75% (relative risk 0·25, 0·13–0·51; p<0·0001). Adverse events occurred in 96 (88%) patients in the teriflunomide group and 47 (82%) patients in the placebo group; serious adverse events occurred in 12 (11%) patients in the teriflunomide group and 6 (11%) patients in the placebo group. Nasopharyngitis, upper-respiratory-tract infection, alopecia, paraesthesia, abdominal pain, and increased blood creatine phosphokinase were more frequent with teriflunomide than with placebo. During the double-blind phase, four patients in the teriflunomide group had pancreatic adverse events (two with acute pancreatitis and two with pancreatic enzyme elevation), of which three events led to treatment discontinuation. Interpretation: No significant difference in time to first confirmed clinical relapse was found, possibly because more patients than expected switched from the double-blind to the open-label treatment period because of high MRI activity. Key secondary imaging analyses and a prespecified sensitivity analysis of probability of relapse or high MRI activity suggest that teriflunomide might have beneficial effects in children with relapsing multiple sclerosis by reducing the risk of focal inflammatory activity. Funding: Sanofi.